Kedudukan Hukum Persewaan Tanah Negara - Iwan Permadi (Perspektif Hukum, 2016)
This paper examines how the legal status of leasing the public land in deal with the State's Right of Controlling is and how the further regulating them in the implementation of regional autonomy is. The used method is a normative legal research with secondary data sources through primary legal materials, secondary and tertiary. The results show that leasing the land that the object is a public land constitutes an action against the law, because the state is in fact not the owner of the land. The state only has the right to control the public land and the only the owner has the right to lease the land. Therefore, there is a smuggling law in case of leasing the public land through enacting the regional regulations that contain the permit to use the public land, that the third parties can use public land but the third party must pay a sum of money.